The 154 MHz radio sky observed by the Murchison Widefield Array: Noise, confusion, and first source count analyses - Franzen, Thomas; Jackson, Carole; Offringa, A.; Ekers, Ronald; Wayth, Randall; Bernardi, G.; Bowman, J.; Briggs, F.; Cappallo, R.; Deshpande, A.; Gaensler, B.; Greenhill, L.; et al. (Oxford University Press, 2016)
© 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society. We analyse a 154 MHz image made from a 12 h observation with the Murchison Widefield Array (MWA) to determine the noise contribution and behaviour of the source counts down to 30 mJy. The MWA image has a bandwidth of 30.72 MHz, a field-of-view within the half-power contour of the primary beam of 570 deg2, a resolution of 2.3 arcmin and contains 13 458 sources above 5s. The rms noise in the centre of the image is 4-5 mJy beam-1. The MWA counts are in excellent agreement with counts from other instruments and are the most precise ever derived in the flux density range 30-200 mJy due to the sky area covered. Using the deepest available source count data, we find that the MWA image is affected by sidelobe confusion noise at the ˜3.5 mJy beam-1 level, due to incompletely peeled and out-of-image sources, and classical confusion becomes apparent at ˜1.7 mJy beam-1. This work highlights that (i) further improvements in ionospheric calibration and deconvolution imaging techniques would be required to probe to the classical confusion limit and (ii) the shape of low-frequency source counts, including any flattening towards lower flux densities, must be determined from deeper ˜150 MHz surveys as it cannot be directly inferred from higher frequency data.